Never good enough because of my race: exploring the impact of interracial relationships on the individual's racial identity in Singapore - Soh, Hui (Nanyang Technological University, 2024)
The paucity of literature addressing racism experienced by individuals in interracial relationships and how racism impacts their racial identity in Singapore persists as a significant deficiency. Existing literature focuses on the role of social networks and network approval in determining the success of interracial relationships, while others acknowledge that racial identity of those in interracial relationships are constantly in flux. However, a critical gap remains in understanding how social networks and the lack of network approval from their partner’s family due to stereotypes and racism shape an individual's racial identity. As such, this paper seeks to elucidate the struggles that individuals in interracial relationships find themselves facing, examining how they make sense of their racial identities having experienced racism from their partner’s family in the Singaporean context